Kaitan Kondisi Oseanografi dengan Komposisi Jenis dan Kelimpahan Makrozoobentos di Perairan Pelabuhan Kota Benteng Kabupaten Selayar - Farid Samawi; Wasir Samad; Sry Swarni Abu Bakar (Jurnal Ilmu Kelautan SPERMONDE, 2016)
This study aims to determine the species composition and density of acrozoobenthos in the waters around Harbor Benteng,Selayar District. Based on the results and discussion can be concluded that the type of macrozoobenthos were found gastropods are equal to 79%; 14% bivalves and crustacean 7%. Diversity of macrozoobenthos in the category of low and there is no dominant species. Oceanographic parameters associated with the density of macrozoobenthos is TSS and DO.